Digital divide among Malaysian tertiary students and its impact on online learning during the covid-19 pandemic - Latha, Subramaniam (2023)
The term “digital divide” evolved from having a simple meaning of “have and have nots” of access to Internet and computers to an indication of disparity in motivational, material access and then to divide in digital skills, digital usage and outcomes of digital use. In this era of digitalisation, information and communication technologies are hailed as empowering and inclusive tools that facilitate and enhance education, economic, political, social and cultural dynamics, but it could not be denied that dependency on ICTs has created an additional new form of exclusion called digital divide. Consequences of digital divide on education is generally very profound, but the impact was felt more by students during the Covid-19 pandemic, as education institutions globally adopted online teaching and learning. Education was digitalized and remote learning was encouraged to accommodate the “new normal” and to facilitate the practice of social distancing, thus, the underlying issue of digital divide should be addressed, as it is a massive threat that could hinder and disrupt students’ online learning. Instances such as the hardship faced by fellow Malaysian student, Veveonah Mosibin’s and many others’ plight during the Covid-19 pandemic indicated that students in higher education institutions are prone to face digital inequality and its perilous consequences on their online tertiary academic journey. This study examined the extent of digital divide among students of higher education institutions in Malaysia and its impact on their online learning during the Covid-19 pandemic by using the framework of Three Levels of Digital Divide. Mean scores were used to measure the scope of digital divide among student respondents. Then, Partial Least Squares-Structural Equation Modelling (PLS-SEM) was employed to test the relationships between different levels of digital divide and their impact on online learning outcomes measured by perceived learning and learning satisfaction. With an exception for motivational access in the first level, this study uncovered the presence of disparities in terms of material access, digital skills, digital usage and online learning outcomes, which indicates digital divide at all three levels among student respondents. Results have also unveiled contradictory findings on the relationships between constructs of digital divide and online learning outcomes. It was found that whilst most hypotheses proposed were supported, however, the relationships between motivational access and digital skills, material access and neither of the online learning outcomes, digital skills and both of the online learning outcomes, digital usage and students’ satisfaction were not supported. This present study uncovered the use of three levels of digital divide framework in the context of online learning. It highlights the importance of tackling digital divide at all three levels for Malaysian university students to attain fruitful online learning outcomes. Moreover, roles of multiple stakeholders were also discussed to bridge the gap of digital divide at all three levels among Malaysian tertiary students, with a great emphasis of efforts needed from governmental/political actors and policy-makers to tackle this grave issue.